E-Retribution as an Effort to Break the Corruption Chain (Study of Market E-Retribution Implementation in Surakarta City) - Kinasih, Wulan (IJCLS (Indonesian Journal of Criminal Law Studies), 2019)
Retribution is one of the most important regional revenues. Managing levies manually has a large potential for fund leakage and transparency issues. This study aims to describe the implementation of e-levies in the traditional markets of Surakarta city as an effort to break the chain of corruption. This research is a qualitative descriptive study. The research was conducted at Klewer Market and Surakarta City trade service. The results of the study indicate that E-retribution can increase transparency, accountability and community participation in supervision so that corruption can be minimized.